Komposisi Musik Ilustrasi Pada Kelompok Teater Kembang SMA N 1 BREBES (Universitas Negeri Semarang, 2020)
Theater is a performing art which in its performance brings a story that is delivered through acting on the stage. Theater performance is inseparable from music as supporting atmosphere. Based on that, this research aims to know the types of illustration music composition in â€œKembangâ€ Theater group from SMA N 1 Brebes. This study used qualitative method. To obtain the accurate data, this study used observation, interview, and documentation. This research consists of data collection, data reduction, data presentation, and conclusion. The result shows that â€œKembangâ€ Theater always makes music composition that is suitable with the theme of the script on their performances. Illustrated music is always played live on stage with consideration of getting maximum results in every scene played. There are various types of illustration music composition in â€œKembangâ€ Theater group. They are opening music, happy music, wistful music, tense music, horror music, romantic music, comical music, sampakan music/convey music, transition music, and closing music. The types of script are divided into two types. There are tragedy script and comedy script. Not all types of Illustration music composition exists in all types of script. For example, sampakan music and comical music that only exist in comedy script.